An Investigation of Macrostructure, Superstructure, and Microstructure on Online News Text (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
This study aimed to analyze the structure of the text in the news texts of tempo.com entitled “Tolak Relokasi Ibu Kota,” published in 2019, in which it highlighted the government’s plan to relocate the capital city of Indonesia. The descriptive qualitative model was used by adapting van Dijk’s approach. The data were analyzed only in terms of the structure of text on online media tempo.com and with the orientation of the descriptive-analytic method. The data of this study were presented qualitatively. The results showed that the journalists of tempo.com media built public opinion in the news negatively. The journalists utilized selected diction, cause-effect organization, and selected speaker’s indirect quotations to produce news texts. Besides, the news was considered in harmony with its mission of providing a multimedia product independent and free from all pressures. The readers were led to a negative image of the government on tempo.com as an active and existent media in voicing justice.